A Polyp Worth Removing: A Paradigm for Measuring Colonoscopy Quality and Performance of Novel Technologies for Polyp Detection. Issue 9 (30th October 2021) - Karnes, William E.; Johnson, David A.; Berzin, Tyler M.; Gross, Seth A.; Vargo, John J.; Sharma, Prateek; Zachariah, Robin; Samarasena, Jason B.; Anderson, Joseph C.
Abstract : Leaving no significant polyp behind while avoiding risks due to unnecessary resections is a commonsense strategy to safely and effectively prevent colorectal cancer (CRC) with colonoscopy. It also alludes to polyps worth removing and, therefore, worth finding. The majority of "worthy" precancerous polyps are adenomas, which for over 2 decades, have received the most attention in performance research and metrics. Consequently, the detection rate of adenomas is currently the only validated, outcome-based measure of colonoscopy demonstrated to correlate with reduced risk of postcolonoscopy CRC. However, a third or more of postcolonoscopy CRCs originate from sessile serrated polyps (SSPs), which are notoriously difficult to find, diagnose and completely resect. Among serrated polyps, the agreement among pathologists differentiating SSPs from non-neoplastic hyperplastic polyps is moderate at best. This lack of ground truth precludes SSPs from consideration in primary metrics of colonoscopy quality or performance of novel polyp detection technologies. By instead leveraging the distinct endoscopic and clinical features of serrated polyps, including those considered important due to proximal location and larger size, clinically significant serrated polyps represent serrated polyps worth removing, enriched with subtle precancerous SSPs. With the explosion of technologies to assist polyp detection, now is the time to broaden benchmarks to include clinically significant serrated polypss alongside adenomas, a measure that is relevant both for assessing the performance of endoscopists, and for assessing new polyp detection technologies.